Unsur Perbuatan Melanggar Hukum Pemerintah Perspektif Peraturan Pelaksana Kriteria Baku Kerusakan Ekosistem Karst - Maulidin, Muhammad; Muhjad, Hadin; Erlina, Erlina (Green Publisher Indonesia, 2025)
The purpose of the study is to analyze and study the laws and regulations that accommodate the protection of karst ecosystems. In addition, this study also aims to analyze the government's actions that are considered negligent because they do not follow up on the mandate of Law number 32 of 2009 concerning Environmental Protection and Management to make implementing regulations through Government Regulations regarding the standard criteria for damage to karst ecosystems whether they are included in illegal acts by the government. This research is a normative legal research, which is a research using a statutory and conceptual approach. According to the results of this study, it was found that there had been a legal vacuum after the promulgation of the UUPPLH. According to the UUPPLH, the government should issue a legal product of a technical and implementing nature in the form of a Government Regulation regarding the standard criteria for damage to the karst ecosystem to determine the extent of damage that can be tolerated by the ecosystem. As long as technical rules have not been promulgated regarding the standard criteria for damage to karst ecosystems, then as long as environmental law enforcement against damage to karst ecosystems due to mining is quite difficult to enforce. The absence of implementing regulations regarding the standard criteria for damage to karst ecosystems can be categorized as unlawful acts by the government (Onrechtmatige Overheidsdaad) because there are legal norms that state that government actions are actions carried out and/or not carried out by the government in order to carry out government. So that if the government's actions can be detrimental and potentially detrimental to the constitutional rights of citizens, it can be classified as an unlawful act by the government.